Любовь Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 1997)
Экземпляры: ЦБ (20131115) / Инвентарный номер: 44684 / Цена: 35.00 / Авт.знак: Д 71 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6